DEVELOPMENT OF AN EDUCATIONAL BOOK ON PHYSICAL FITNESS COMPONENTS FOR ELEMENTARY SCHOOL STUDENTS - Putri Mas Bintania,; Anggri Dwi Nata,; Rahmat Sanusi, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
This research is motivated by the low understanding of students towards the components of physical fitness and the lack of interesting learning media in supporting the learning process of PJOK in State Elementary School 001 Meral Barat. This type of research is a development research (research and development) using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The population in this study were 23 people consisting of PJOK teachers and elementary school students. The sample selection used purposive sampling involving 22 people. Data analysis techniques by looking at the N-Gain value. The validation results from the material validator obtained a score of 88% with a very feasible description. The results of the effectiveness test on a small scale with an N-Gain value obtained a value of 0.75 with a High level criterion and the results of the effectiveness test on a large scale with an N-Gain value obtained a value of 0.72 with a High level criterion.